The EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AND GOOD CORPORATE GOVERNANCE IMPLEMENTATION ON RESPONSE COEFFICIENT EARNINGS (ASEAN COUNTRY CROSS STUDY 2016-2018) - RENALITA, PUTRI (Archives of Business Research, 2019)
Abstract This study aims to analyze the effect of disclosure of Corporate Social Responsibility and Good Corporate Governance on Earning Response Coefficient. The sampling technique used was purposive sampling. The research was conducted on Manufacturing Companies in the Countries of Indonesia and Malaysia which were included in the ASEAN CG Scorecard with the 2016-2018 research period. The estimation of the research model used is multiple regression analysis. The purpose of this study is to determine whether disclosure of Corporate Social Responsibility and Good Corporate Governance has an effect on Earning Response Coefficient. This study involved 3 (three) variables consisting of 1 (one) dependent variable, 2 (two) independent variables (independent), and the dependent variable in this study was Earning Response Coefficient. The independent variable in this study is Corporate Social Responsibility and Good Corporate Governance. The results of this study indicate that Corporate Social Responsibility and Good Corporate Governance have an effect on Earning Response Coefficient.